A SOCIOLINGUISTICS ANALYSIS OF SPEECH STYLE IN ELLEN'S BRIELLE INTERVIEW - Hasan, Hani Firlyali; S, Dwi Triana; Matanari, Desna Uli; Simangunsong, Anisyah Srirezeki; Rangkuti, Rahmadsyah (Ma Chung Press, 2024)
This study conducts a sociolinguistic analysis of the speech styles exhibited during the interview between Ellen DeGeneres and three-year-old Brielle on The Ellen Show. Utilizing a qualitative case study approach, the research examines the dynamics of spoken language within a popular media context, focusing on how age and social context influence communication styles. The analysis identifies five distinct speech styles based on Joos's (1967) classification: formal, casual, consultative, intimate, and frozen. The findings reveal that Ellen employs a blend of formal and casual styles when introducing Brielle, transitioning to a more relaxed and engaging tone as the conversation progresses. Brielle's responses reflect a casual style that fosters relatability while showcasing her knowledge of complex subjects like the periodic table. The consultative style emerges during educational exchanges, where both speakers engage in informative dialogue. Additionally, intimate moments are highlighted through interactions with Brielle's mother, emphasizing familial closeness. This study contributes to the understanding of how speech styles adapt in response to varying social contexts and age differences, illustrating the intricate relationship between language and interpersonal dynamics in televised interviews. The results underscore the effectiveness of Ellen's communicative approach in creating an inviting atmosphere that resonates with a diverse audience, ultimately enhancing viewer engagement and understanding of complex topics through accessible dialogue